Prevalence and Distribution of Cracked Posterior Teeth among Adult Patients - Temiloluwa Olawale Ogundare; Deborah Mojirade Ajayi; Paul Ikhodaro Idon; Cornelius Tokunbo Bamise; Adeleke Oke Oginni; Temitope Ayodeji Esan (Scientific Research Publishing, 2024)
13p